The regulation of cannabis in Europe: of highs and laws - Hofmann, Robin (Routledge Focus, 2025)
"Changing attitudes towards cannabis across Europe are challenging old convictions of drug prohibition and making space for new approaches to the drug. This book delves into the evolving landscape of cannabis regulation across Europe and the world. Starting with Germany's push for full legalization, the work highlights the hurdles faced by policymakers, offering a detailed analysis of the international and European frameworks that restrict drug policy reform and discussing potential loopholes to avoid them. The case of Germany and its struggle with cannabis reform serves as a valuable blueprint with guidance for other states considering implementing more progressive approaches to drugs. The volume explores the complexities of cannabis regulation in a concise and approachable way, targeting not only legal professionals but also policymakers and readers with an interest in the societal dynamics of drug policy reforms and how these are shaped by the European Union and international law. The book will be of interest to a broad audience that includes legal scholars and practitioners, students of criminology, international law, and European law or those with an interest in EU security and health policies"--